Clinical effect of E-series of prostaglandin receptor 2 and epidermal growth factor receptor signal pathways in the development of esophageal squamous cell carcinoma. Issue 4 (1st June 2014) - Xu, K.-K.; Tian, F.; Chang, D.; Gong, M.; Fan, J.-Q.; Wang, T.-Y.
Summary: Signal pathways mediated by epidermal growth factor receptor (EGFR ) and E -series of prostaglandin receptors (EPs ) are closely correlated to the pathogenesis of tumor. This experiment was designed to investigate the expression and clinical significance of EP 2 and EGFR in esophageal squamous cell carcinoma (ESCC ). Tissue samples were collected reterospectively from 87 patients with ESCC (first diagnosed). The patients were followed up for 5 years after radical surgery. The expression of EP -2 and EGFR were examined by tissue chip technology and immunohistochemistry methods. Clinicopathological and prognostic impact were evaluated. Overexpression of EGFR and EP -2 was more observed in ESCC than the control group (58.6% vs. 13.9%; 52.9% vs. 4.88%, P < 0.001, respectively); which correlated with tumor infiltration depth, lymph node metastasis, and tumor-lymph node-metastasis staging. Both the EP -2 and EGFR overexpression were detected in 39 specimens and exhibited the positive correlation ( P < 0.001, r = 0.404). Overexpression of EP2 and EGFR exhibited significant correlation with worse 5-year overall survival than those with negative result (17.6% vs. 27.8%, P = 0.011; 10.9% vs. 34.1%, P < 0.001, respectively). C ox proportional hazard model showed that the T -staging, lymph node metastasis, and EGFR overexpression were the independent risk factors of the prognosis. The present study exhibited that the overexpression of EP2 and EGFR in ESCC tissues might play an important role in carcinogenesis and the progression of ESCC .